2002
DOI: 10.1096/fj.02-0487fje
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the tumor vasculature functionality by ionizing radiation accounts for tumor radiosensitization and promotes gene delivery

Abstract: The ultimate goal of radiotherapy is to induce irreversible damages in genetically unstable, fast-growing cancer cells while minimizing the cytotoxic effects on host tissues. The satus of the tumor vasculature is particular because it is located within the tumor but mostly arises from host cells. The aim of this study was to characterize the effects of low-dose irradiation on the function of endothelial cells lining tumor vessels. Using isolated arterioles mounted on a pressure myograph, we first documented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 31 publications
1
61
0
Order By: Relevance
“…However, it is not uncommon to find mature blood vessels with smooth muscle layers and neural junctions inside slowly growing tumors (1). It was previously confirmed that these arterioles remain sensitive to vasomodulation under tumor co-option but also are subject to major adaptations to the tumor microenvironment (26,27). Here, we found that BoNT-A inhibits the release of noradrenaline, a major endogenous vasomodulator that is responsible for the maintained sympathetic vascular tone through activation of vascular smooth muscle a-adrenoceptors.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is not uncommon to find mature blood vessels with smooth muscle layers and neural junctions inside slowly growing tumors (1). It was previously confirmed that these arterioles remain sensitive to vasomodulation under tumor co-option but also are subject to major adaptations to the tumor microenvironment (26,27). Here, we found that BoNT-A inhibits the release of noradrenaline, a major endogenous vasomodulator that is responsible for the maintained sympathetic vascular tone through activation of vascular smooth muscle a-adrenoceptors.…”
Section: Discussionmentioning
confidence: 98%
“…Determination of cell oxygen consumption was carried out using EPR as previously reported (49). Briefly, 2 × 10 7 viable cells/ml were sealed in glass capillary tubes in the presence of 0.2 mM of the O2 sensor 4-oxo-2,2,6,6-tetramethylpiperidine-d-15 N-1-oxyl (CDN isotopes) and with CHC where indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular basis of the increase in pO 2 was recently investigated in a study combining EPR oximetry and molecular biology: it turns out to be nitric oxide mediated by changes in expression of eNOS and caveolin. 235 Open square: RX þ insulin þ pre-treatment with L-NAME. See Jordan et al 66 for details.…”
Section: Radiotherapymentioning
confidence: 99%